Capital Penetration And Coping Strategies Of Traditional Hindu Fisherfolk In Bangladesh - Rashid, Mohammed Mamun Or (2022)
Bangladesh is a lower-middle-income country in South Asia where traditional fishermen, herein, Jaladas are at risk of chronic poverty. This study was conducted in two Jaladas villages to identify the socio-economic transformations caused by the inflows of capitals from different actors and the roles of various market functionaries, traditional social institutions, and power relations. Moreover, it aims to examine the coping strategies; and providing policy recommendations for their inclusion and wellbeing. This study adopted the qualitative research design, specifically the Key Informant Interview (KII), Focus Group Discussion (FGD) and household level case studies. A random survey of 100 households was conducted. The findings revealed that NGO-led interventions increase awareness, leadership development, education, access to health and sanitation facilities, and provide alternative employment skills to improve the quality of life in one of the villages studied. In the meantime, the increase numbers of commercial entrepreneurs have led higher over-exploitation of fisheries resources where powerful market functionaries control the fish marketing structure.